Exploratory study in universitary students. Socio-demographic references and career choice (Praxis Educativa, 2014)
In this paper the problem investigated is linked to the need to know the characteristics of young people entering university life and some of their psychosocial references. Also, we identify characteristics on the population of different careers so we could relate particular psychosocial characteristics to personal and school paths. In addition, we aimed to investigate distinctive features of each population to establish relationships between prior arrangements, career choice and college journey. We worked with the population of three different careers: Psychology, Graphic Design and Public Accountant, at a private university in the city of Córdoba. The methodology used was a mixed approach, using surveys and interviews. In this opportunity, we present the first results concerning sociodemographic aspects, career choices and changes occurring in the new student life.
Keywords: university life; career choice; students; habitus; youngsters